SOCIAL IMPACT ANALYSIS AND REPLACEMENT COST OF POST SAND MINING DAMAGE PT.X NANJUNG RIVER VILLAGE, MATAN HILIR SUB-DISTRICT - Akbar, Muhammad Fadli; Akbar, Aji Ali; Utomo, Kiki Prio (Komunitas Menulis dan Meneliti (Kolibi), 2024)
Mining operations always involve a number of environmental interactions. Sand mining operations degrade the surrounding environment, causing significant physical damage to the landscape and possibly making the area more vulnerable to air pollution, flooding and landslides. A national private company called PT X has conducted exploration and feasibility studies. In calculating losses due to pollution, the analysis method is the replacement cost method. The disease cost analysis approach is used in data analysis to calculate economic losses due to post-mining pollution. From the results of the analysis that has been carried out, it is known that the location of the mining business activity has an estimated quartz sand reserve of 7,708,637 tons with a mining plan of 300,000 m3 / year and this calculation shows that each resident is entitled to receive a replacement cost of Rp.1,542,807 / month. The result of the calculation of the total environmental damage recovery value is Rp.1,482,521,465. The results of the post-mining damage analysis show that the application of mining can have a negative impact on the environment and society.